Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Di Kampung Lengkong, Kecamatan Cigombong, Kabupaten Bogor, Jawa Barat - Ade Arqam Hidayat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of the study was to see the extent of community participation in the development of tourist villages in the village of Lengkong, Cigombong, Bogor Regency, West Java and what factors were inhibiting and supporting it. This study uses data collection through in-depth interviews to each resource person who is considered capable of providing information in accordance with research needs.The resulting data shows that community participation in the Lengkong village in terms of developing a tourist village is still very low. This can be seen from community participation in development planning, community participation in the implementation of development and community participation in monitoring and evaluating what has been done. There are supporting factors such as natural resources, awareness of the administrators, age, duration of stay, the role of the STIAMI Institute, and the role of the government as well as the Tourism Village Association. Whereas the factors that hinder community participation are education, lack of motivation, work, and communication.